2021
DOI: 10.1007/s00216-021-03177-y
|View full text |Cite
|
Sign up to set email alerts
|

3D-surface MALDI mass spectrometry imaging for visualising plant defensive cardiac glycosides in Asclepias curassavica

Abstract: Mass spectrometry–based imaging (MSI) has emerged as a promising method for spatial metabolomics in plant science. Several ionisation techniques have shown great potential for the spatially resolved analysis of metabolites in plant tissue. However, limitations in technology and methodology limited the molecular information for irregular 3D surfaces with resolutions on the micrometre scale. Here, we used atmospheric-pressure 3D-surface matrix-assisted laser desorption/ionisation mass spectrometry imaging (3D-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Ritmejeryte ̇et al revealed a tissue-specific distribution of cyanogenic glycosides (defence metabolites that deter herbivores by releasing hydrogen cyanide upon hydrolysis) in stigma cells and pollen of cyanogenic florets of the genus Lomatia and substantial variation in their concentrations within florets suggesting that their allocation is under strong selection (Ritmejeryte ̇et al, 2020). Dreisbach et al indicated an increased latex flow rate towards the point of damage leading to an accumulation of cardiac glycosides and other defence metabolites in the affected area of the leaves of Asclepias curassavica (Dreisbach et al, 2021). Numerous studies have shown that MALDI-MSI is useful in plant science for obtaining molecular information on topographical features at the cellular level, and the fine visualisation of metabolites demonstrates the advantages of MALDI-MSI for the study of plant defence mechanisms.Therefore, taken together, our results support the hypothesis that mescaline is more prevalent in the active meristems, epidermal tissues, and protruding parts of the cactus, which are all areas that are vulnerable to animal browsing.…”
Section: Discussionmentioning
confidence: 99%
“…Ritmejeryte ̇et al revealed a tissue-specific distribution of cyanogenic glycosides (defence metabolites that deter herbivores by releasing hydrogen cyanide upon hydrolysis) in stigma cells and pollen of cyanogenic florets of the genus Lomatia and substantial variation in their concentrations within florets suggesting that their allocation is under strong selection (Ritmejeryte ̇et al, 2020). Dreisbach et al indicated an increased latex flow rate towards the point of damage leading to an accumulation of cardiac glycosides and other defence metabolites in the affected area of the leaves of Asclepias curassavica (Dreisbach et al, 2021). Numerous studies have shown that MALDI-MSI is useful in plant science for obtaining molecular information on topographical features at the cellular level, and the fine visualisation of metabolites demonstrates the advantages of MALDI-MSI for the study of plant defence mechanisms.Therefore, taken together, our results support the hypothesis that mescaline is more prevalent in the active meristems, epidermal tissues, and protruding parts of the cactus, which are all areas that are vulnerable to animal browsing.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 38 , 46 48 A typical multiple-element microscope objective has a high numerical aperture but small working distance that can be used in transmission mode ablation but otherwise limits access to the sample. 49 51 A central hole can be cut through a high numerical aperture objective to allow the ablated material to pass through, 52 57 but viewing the ablation process is otherwise obscured.…”
Section: Introductionmentioning
confidence: 99%
“…Laser ablation, with a small spot size that approaches the micrometer diffraction limit of a mid-IR laser, requires an objective with a large numerical aperture and a large working distance for viewing the tissue and collection of the ablated material. Single focusing elements are simple and provide a working distance of several centimeters but can only focus the laser to a spot size of approximately 100 μm. ,, A typical multiple-element microscope objective has a high numerical aperture but small working distance that can be used in transmission mode ablation but otherwise limits access to the sample. A central hole can be cut through a high numerical aperture objective to allow the ablated material to pass through, but viewing the ablation process is otherwise obscured.…”
Section: Introductionmentioning
confidence: 99%
“…However, using 3D LC/MS framework is giving new frontiers for imaging the spatial distribution of small molecules in plant tissue. In this respect atmospheric-pressure 3D-surface matrix-assisted laser desorption/ionization mass spectrometry imaging (3D-surface MALDI MSI) was used to investigate plant chemical defense at the topographic molecular level for the Asclepias curassavica L. It was established that the mechanical damage stimulated the secretion of defense metabolites, the dominant of which were cardiac glycosides [ 79 ].…”
Section: Metabolic Profiling Of Nutritional Crops and Medicinal Plantsmentioning
confidence: 99%
“…Integration of metabolomics data with bioassays results shortens the drug discovery process through assisting the bioassay-guided fractionation (biochemometrics approach). Additionally, plant metabolomics is an indispensable tool for defining or refining pathway structure [ 73 , 74 ], increasing specific SMs production through metabolic engineering [ 75 ], as well as assuring the quality and safety of plant-derived natural products [ 76 79 ]. Selected studies representing the application of metabolomics in medicinal plant research are presented in Supplementary Table S2.…”
Section: Metabolic Profiling Of Nutritional Crops and Medicinal Plantsmentioning
confidence: 99%